Therapists' experience of training and implementing an exoskeleton in a rehabilitation centre. Issue 7 (27th March 2022) - Mortenson, W. Ben; Pysklywec, Alex; Chau, Leena; Prescott, Michael; Townson, Andrea
Abstract: Background: Lower limb exoskeletons are a recent intervention promoted to improve gait disorders. Available research has focused on clinical outcomes; however, little is known about therapists' experiences using the device in practice. Purpose: We explored the implementation of an exoskeleton at a tertiary rehabilitation center. Method: In this longitudinal qualitative study we conducted semi-structured interviews with 10 therapists. One group of therapists was formally trained using the device, whereas the other group only had clinical exposure to the device. The interviews were transcribed, coded, and analyzed for themes. Results: Three main themes emerged: (1) A steep learning curve described challenges in learning to use the exoskeleton. (2) One step at a time illustrated the complex process of incorporating the exoskeleton in daily work. (3) Not a magic bullet revealed the tensions using this emergent technology in practice. Conclusion: The exoskeleton represents one of the most complicated and labor-intensive interventions provided by therapists. Implementation requires substantial resources, raising questions regarding its efficacy and cost-effectiveness relative to other approaches. Until more evidence becomes available around the use and effectiveness of this rapidly evolving technology, therapists must contend with a high degree of uncertainty. IMPLICATIONS FOR REHABILITATION: Using a lower limb exoskeleton may reduce physical demands on therapists in high-intensity rehabilitation programs that involve repetitive, effortful movements. However, a number of potential barriers to implementing the exoskeleton into practice need to be taken into consideration, including calibration time, intensive training required to become qualified to administer the intervention, the cost of the device, and comfort and safety of the device affecting user acceptance and uptake. Therapists also need to manage patient expectations related to outcomes related to use of exoskeletons.